Enhancing cardiovascular patients’ knowledge of air pollution: a pilot study evaluating the impact of an educational intervention in cardiac rehabilitation - Supervia, Marta; Bomtempo, Ana Paula Delgado; Gómez, Eduardo; Bonikowske, Amanda R.; Arroyo-Riaño, Maria Olga; Ghisi, Gabriela Lima de Melo (Frontiers in Rehabilitation Sciences, 2024)
IntroductionAir pollution poses significant risks to cardiovascular health, yet patients often lack comprehensive knowledge about its impact and mitigation strategies. This study aims to evaluate the effectiveness of an educational intervention within a cardiac rehabilitation (CR) context in enhancing patients’ understanding of air pollution and its cardiovascular effects.MethodsA pre-post pilot study was conducted from February 2021 to June 2021 at the Gregorio Marañón University General Hospital, Madrid, Spain. A total of 43 patients with cardiovascular disease attending CR were enrolled. Participants received a 1-h educational intervention delivered either in-person or online, focusing on the effects of air pollution and strategies to reduce exposure. Pre- and post-intervention questionnaires assessed participants’ knowledge and perceptions. Descriptive statistics were used to analyze changes in awareness and understanding.ResultsInitially, participants demonstrated a high level of awareness about the health impacts of air pollution, with 100% acknowledging its effects on health. However, detailed knowledge about specific concepts such as the Air Quality Index (AQI) and particulate matter (PM2.5) was limited. Post-intervention, there was a significant increase in knowledge, with familiarity with AQI rising from 61% to 81% (p = 0.02) and understanding of PM2.5 improving from 28% to 58% (p = 0.01). This indicates that the educational intervention effectively bridged gaps in understanding and reinforced the importance of environmental factors in cardiovascular health management.DiscussionThe pilot study highlights the critical role of targeted education in improving patient awareness and knowledge about air pollution. The significant improvement in understanding key concepts underscores the need for broader educational initiatives that extend beyond CR programs. Future research should explore the impact of such interventions on long-term health outcomes and consider expanding educational efforts to include healthcare providers and family members.